Namets! (Cinemalaya, 2008)
Namets! follows the ongoing flirtation between Jacko and Cassie, two Negrenses who grew up in Bacolod City, and whose lives revolves around food. Trouble starts when Jackos loses his Italian restaurant, Puccinis', to a giant cockfighting debt. The money-lender Dolpo (Peque Gallaga) takes control of Puccinis and hires Cassie as a consultant for a total restaurant makeover.